Broadband, High‐Sensitivity Graphene Photodetector Based on Ferroelectric Polarization of Lithium Niobate. Issue 16 (1st June 2021) - Guan, Heyuan; Hong, Jiyu; Wang, Xiaoli; Ming, Jingyuan; Zhang, Zilong; Liang, Aijie; Han, Xinyang; Dong, Jiangli; Qiu, Wentao; Chen, Zhe; Lu, Huihui; Zhang, Han
Abstract: 2D graphene has attracted extensive attention as a promising candidate for high‐performance photodetectors because of its superior optoelectronic properties. However, the realization of high‐sensitivity broadband graphene photodetectors remains a challenge. Lithium niobate (LiNbO3 ) has the advantages of spontaneous polarization, high dielectric constant, and high voltage electric coefficient, and it can improve the photoelectric detection characteristics of graphene by polarized doping. In this work, n‐ and p‐doping of graphene is demonstrated at the same time with the help of local ferroelectric polarization of x‐cut LiNbO3 . This high‐sensitivity and broadband p–n junction photodetector shows a wide detection range of 405 to 2000 nm, a responsivity of ≈2.92 × 10 6  A W −1 at an incident power of 24 pW (λ = 1064 nm), and a high detectivity of ≈8.65 × 10 14  Jones. In particular, a fast rise/decay time of ≈23 ms/≈23 ms is achieved. The graphene‐based LiNbO3 (bulk) photodetector shows higher responsivity​, and the graphene‐based LiNbO3 (film) photodetector a faster response time. This work not only deepens and expands the basic research on 2D materials and ferroelectric materials, but also demonstrates the great potential of doped graphene materials for high‐performance photodetection. Abstract : A high‐sensitivity and broadband p–n junction graphene‐based LiNbO3 photodetector is demonstrated, showing a wide detection range of 405 to 2000 nm, a responsivity of ≈2.92 × 10 6  A W −1 at an incident power of 24 pW (λ = 1064 nm), and a high detectivity of ≈8.65 × 10 14  Jones.